(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Innovative technology rolled out progressive improvements in our lives. We can’t deny the fact that technology and innovation assumed a significant part of our lives. Despite this, numerous innovation-based technologies and businesses never arrive at their maximum capacity, and some are just dismissed because they fail to access the readiness and acceptance of users. Although various other studies presented a literature review on a similar topic most of the talks on a specific technology and the horizon of the study were limited to a few years. Also, previous studies in our knowledge preserved literature on the technology acceptance model or technology readiness model separately. This study aims at providing a comprehensive review of all technologies without any discrimination. The current study presents the results of 112 academic papers selected from the large pool of databases on technology readiness, technology acceptance, and technology readiness and acceptance model. In this study, we are trying to present a systematic literature review on the technology readiness and technology acceptance model for the last 20 years. This paper is going to add value to the available literature on TAM and TR models and will help further to scholars working on these models.